Within-day and between-day Reproducibility of Baroreflex Sensitivity in Healthy Adult Males - Reynolds, L. J.; De Ste Croix, M.; James, D. V. B. (International Journal of Sports Medicine, 2016)
Within-day and between-day reproducibility of supine and tilt baroreflex sensitivity were investigated utilising sequence and spectral indices in 46 healthy adult males employing 3 repeat measures; baseline, +60 min and +24 h. Reproducibility was assessed via the 95% limits of agreement and by the technical error of the measurement. For spectral parameters, the limits of agreement indicated same day was marginally better than between-day reproducibility. For sequence parameters, between-day had marginally better agreement than same-day reproducibility. Tilt markedly improved reproducibility across all outcome measures. Precision expressed by the technical error of the measurement for all spectral outcomes was good in both supine and tilt baroreflex sensitivity (<6%). Precision was lower, but acceptable, for sequence baroreflex sensitivity outcomes in both positions (<11%). Baroreflex sensitivity transfer gain provided the best agreement and reproducibility during supine and tilt conditions. These findings suggest time and spectral techniques may be employed to assess within-day and between-day baroreflex sensitivity changes in healthy individuals. The inclusion of a tilt manoeuvre may improve the reproducibility of the outcome measure, which may aid in the detection of modest baroreflex sensitivity changes in studies employing limited sample sizes.
Keywords: reliability; repeatability; sequence; spectral; supine; tilt